PEMBERIAN GANTI KERUGIAN DALAM PENGADAAN TANAH DI BAWAH 5 (LIMA) HEKTAR DI KOTA BEKASI (STUDI KASUS PROYEK PEMBANGUNAN INSTALASI PENGELOLAAN AIR (IPA)): Granting of Compensation in Land Procurement under 5 (Five) Hectars in Bekasi City (Case Study of Water Management Instalation Development Project) - Sari, Fary Fitriana Gita; Sihombing, Irene Eka (Faculty of Law, Universitas Trisakti, 2024)
The purpose of this study is to describe the provision of compensation in land acquisition under 5 (five) hectares in Bekasi City and in this case makes the author conduct further research with the formulation of the problem whether the process of providing compensation in land acquisition under 5 (five) ) hectares in Bekasi City (Case Study of the Water Management Installation Project Development Project is in accordance with Law Number 2 of 2012 and how to provide compensation in the procurement of land under 5 (five) hectares in Bekasi City (Case Study of the Installation Construction Project Water Management in terms of the position of the community with ownership status of Freehold Land and State Land.The research conducted is normative legal research, with the nature of descriptive research, the type of data used is secondary data.The research is conducted qualitatively by drawing deductive logical conclusions. The results of the research are that the process of providing compensation to the project is in accordance with Law Number 2 of 2012, but in the process of providing compensation there are obstacles at the deliberation stage where the community objects to the results of the compensation assessment and also to the people who use the land and constructing buildings on state land The author's conclusion regarding the obstacles that have occurred have been resolved by the land procurement committee.